Root Words and Derived Words in Indonesian Language Textbooks for Grades 1 and 2: Morphological Study - Hanun Zahronida; Abdul Kholiq (Raja Zulkarnain Education Foundation, 2026)
This study aims to describe the use of root words and derived words in Indonesian language textbooks for grades 1 and 2 of elementary school and to compare them based on morphological analysis. The method used is quantitative with a descriptive-comparative approach. Data collection techniques were carried out through documentation techniques using the